2012
DOI: 10.1002/j.1532-2149.2011.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in analgesic response to ibuprofen are influenced by expectancy: A randomized, crossover, balanced placebo‐designed study

Abstract: We found no sex difference in baseline pain threshold or tolerance levels. When partitioned by sex and expectancy state, analgesia only occurred in males during positive expectancy states at 2, 3 and 4 h post-placebo, and at 1 and 2 h post-ibuprofen. The time course of analgesic action in males was as expected considering the pharmacokinetic profile of ibuprofen. Our study found that dosages of 800 mg of ibuprofen are ineffective in producing analgesia in women regardless of their expectations. We hypothesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 33 publications
(44 reference statements)
3
50
0
1
Order By: Relevance
“…In the current study indomethacin lacked activity against paclitaxel-induced thermal hyperalgesia in female mice but had some activity against the hyperalgesia in male mice. Our findings concur with those of other groups that reported sex differences in response of humans to the analgesic activities of NSAIDs, where some NSAIDs were found to be ineffective against pain in females whilst they were effective in males293031.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study indomethacin lacked activity against paclitaxel-induced thermal hyperalgesia in female mice but had some activity against the hyperalgesia in male mice. Our findings concur with those of other groups that reported sex differences in response of humans to the analgesic activities of NSAIDs, where some NSAIDs were found to be ineffective against pain in females whilst they were effective in males293031.…”
Section: Discussionsupporting
confidence: 92%
“…However, the study did not distinguish specifically between OTC codeine use and other OTC analgesics. It has been suggested that psychological factors play an important role in determining analgesic response, with sex differences observed between males and females, potentially leading to differences in medicine choice and access patterns [39]. Furthermore, in the last 10 years, changing patterns have been observed among people presenting to treatment services for codeine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 4 shows the results of this search, in which only seven studies were found to have used one of these designs in placebo analgesia (Aslaksen, Zwarg, Eilertsen, Gorecka, & Bjørkedal, 2015; Atlas et al, 2012; Berna et al, 2017; Butcher & Carmody, 2012; Kam-Hansen et al, 2014; Lund, Vase, Petersen, Jensen, & Finnerup, 2014; Schenk, Sprenger, Geuter, & Buchel, € 2014). …”
Section: Current Evidencementioning
confidence: 99%
“…Four of the seven studies used the balanced placebo design (Aslaksen et al, 2015; Butcher & Carmody, 2012; Kam-Hansen et al, 2014; Schenk et al, 2014), while two used the balanced open-hidden design (Atlas et al, 2012; Lund et al, 2014). The final study conducted by Berna et al (2017) used a novel design here described as a “balanced active placebo design.” In this variation of the balanced placebo design, receipt of an active treatment or placebo are factorially crossed with administration of an active placebo or placebo, with the second factor replacing the instructions of treatment allocation typical of the balanced placebo design.…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation